Mechanisms of human histone and nucleic acid demethylases. - Walport, L; Hopkinson, R; Schofield, C (2012)
The discovery that protein and nucleic acid demethylation is common opens up the possibility of 'methylation cycles' of functional importance, including in the regulation of gene expression. The mechanisms of known demethylases can be broadly divided into those involving nucleophilic catalysis and those involving oxidative catalysis. The latter group appear more common; they produce formaldehyde as a co-product. Nucleophilic demethylases include those proceeding via irreversible S-methylation and methyl esterases. In addition to the direct reversal of methylation, demethylation can occur concurrent with loss of other groups, such as in methylarginine hydrolysis, oxidation of N(ɛ)-methyllysine to allysine, and indirectly, for example via base-excision repair. We discuss chemically viable mechanisms for biological demethylation and summarise mechanistic knowledge of the major known families of demethylases.